SCIENTIFIC METHOD IN RESEARCH:ESSENTIAL TECHNIQUES AND METHODS (Ustozlar uchun, 2025)
This article provides a comprehensive analysis of the stages and levels of the scientific research process based on modern scientific and methodological approaches. Particular attention is paid to identifying research problems, formulating scientific hypotheses, selecting appropriate research methods, collecting and processing empirical data, systematically analyzing the obtained results, and implementing the findings in practice. In addition, the theoretical foundations of fundamental, applied, and innovative research levels are examined, and their scientific and practical significance is substantiated.